2002
DOI: 10.1038/nrn753
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of CaMKII function in synaptic and behavioural memory

Abstract: Long-term potentiation (LTP) in the CA1 region of the hippocampus has been the primary model by which to study the cellular and molecular basis of memory. Calcium/calmodulin-dependent protein kinase II (CaMKII) is necessary for LTP induction, is persistently activated by stimuli that elicit LTP, and can, by itself, enhance the efficacy of synaptic transmission. The analysis of CaMKII autophosphorylation and dephosphorylation indicates that this kinase could serve as a molecular switch that is capable of long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,516
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,705 publications
(1,554 citation statements)
references
References 123 publications
27
1,516
1
10
Order By: Relevance
“…Other regulators of NR2B include the calcium-calmodulin-dependent protein kinase II (CAMKII) dependent phosphorylation (23). Recently, Guilland (24) demonstrated that the CAMKII dependent phosphorylation of Ser 1029 on KIF17 is responsible for the ultimate release of NR2B, the KIF17 cargo.…”
Section: Commentmentioning
confidence: 99%
“…Other regulators of NR2B include the calcium-calmodulin-dependent protein kinase II (CAMKII) dependent phosphorylation (23). Recently, Guilland (24) demonstrated that the CAMKII dependent phosphorylation of Ser 1029 on KIF17 is responsible for the ultimate release of NR2B, the KIF17 cargo.…”
Section: Commentmentioning
confidence: 99%
“…substrates that coordinates a variety of neuronal functions such as gene expression, membrane excitability, and neuronal transmission (Lisman et al, 2002). Multiple isoforms of CaMKII exist and the a isoform is abundantly expressed in forebrain neurons (Lisman et al, 2002).…”
Section: Cocaine-induced and D1 Receptor-mediated Gene Expression D Zmentioning
confidence: 99%
“…Multiple isoforms of CaMKII exist and the a isoform is abundantly expressed in forebrain neurons (Lisman et al, 2002). Together, changes in the expression of these molecules can change the responsiveness of the D1 receptor-expressing neurons to further neuronal stimulation.…”
Section: Cocaine-induced and D1 Receptor-mediated Gene Expression D Zmentioning
confidence: 99%
See 1 more Smart Citation
“…While the phenomenon of sustained EADs postmitochondrial repolarization in cardiomyocytes needs further experimental verification, it may indeed occur in cells undergoing oxidative stress such as ischemia reperfusion, as a result of the specific property of CaMKII as “a memory molecule.”60 The memory refers to the autophosphorylation‐mediated sustained CaMKII activation even after the dissociation of Ca 2+ /CaM or the fall of Ca 2+ concentration to baseline levels, which is essential for memory storage in the brain. Recently, Song et al61 showed that short‐term (5 minutes) ROS exposure caused persistent (more than 60 minutes) activation of I CaL in isolated rat cardiomyocytes, likely via the oxidative stress–induced sustained CaMKII activation, indicating that CaMKII may act as a redox‐sensitive “memory molecule” in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%